Religious (in)tolerance in digital narratives : a critical analysis of how religious studies professionals can play a role in the responsible use of digital narratives - Beyers, Jaco (University of Pretoria, 2025)
Thesis (PhD (Religion Studies))--University of Pretoria, 2024.